Integrated reporting as a strategy for firm growth: Multiple case study in Colombia (2017)
Purpose - The purpose of this paper is to evaluate the implementation of the integrated reporting (IR) framework in a group of Colombian enterprises. Design/methodology/approach - This is a multiple-case study in six enterprises that use the IR framework. The selected enterprises, all of which were located in either Bogota or Medellin, were Argos, EEB, EPM, ISA, Nutresa and Ocensa. The authors conducted individual interviews of reporters and performed a documentary analysis. Findings - The few Colombian firms that use the IR framework all have ambitious expansion goals in the medium term. The main reason for the adoption of the IR framework in these firms is that it facilitates access to resources from new foreign investors. Research limitations/implications - Since the framework was published recently, only a few Colombian firms follow it, and several of them do not apply all of its components. In the future, there will be more reports and a higher level of framework application. Practical implications - In the firms studied, the IR framework is an important tool to support the search strategies of new sources of financial capital. Social implications - If the use of the International Integrated Reporting Council (IIRC) framework were to diminish the application of the GRI, firms would be less likely to evaluate the impact of their activities on numerous stakeholders (other than shareholders). Originality/value - This is the first Colombian study of IR to include both documentary analysis and personal interviews. © Emerald Publishing Limited.